2014
DOI: 10.18016/ksujns.55749
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Chlorophyll Pigments in Virgin Olive Oil

Abstract: Abstract:The aim of the present study was to determine the changes in the chlorophyll content and the K 232 and K 270 specific extinction coefficient values in virgin olive oil (VOO) subjected to high temperatures for 24 h. VOO, was obtained from Kahramanmaraş city, Turkey, and subjected to 150, 160, 170, 180. 190 and 200ºC for 2, 4, 6, 8, 10, 12 and 24 h, and the chlorophyll content and the K 232 and K 270 specific extinction coefficient values were determined. The chlorophyll content of VOO decreased signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In comparison with literature, Rasul and Inanc [ 55 ] showed that heating VOO to high temperatures (≥150 °C) results in a significant decrease in its chlorophyll content (about 99.5% after heating for 24 hr. at 200 °C).…”
Section: Resultsmentioning
confidence: 64%
“…In comparison with literature, Rasul and Inanc [ 55 ] showed that heating VOO to high temperatures (≥150 °C) results in a significant decrease in its chlorophyll content (about 99.5% after heating for 24 hr. at 200 °C).…”
Section: Resultsmentioning
confidence: 64%
“…Both curcuminoids and chlorophyll, the primary pigments of leaves, are relatively nonpolar, so they are not easily taken by the water during the extraction process [13,14]. Furthermore, chlorophyll started to be degraded upon heating at 180°C for 24 hours, while curcuminoid was degraded after 3 min heating at 180°C [15,16]. Hence, the extracted pigments were likely stable under the extraction temperature used in this study.…”
Section: Resultsmentioning
confidence: 92%
“…Our results indicated significantly (p < 0.05) decreased chlorophyll contents in almost all evaluated samples (Table 7). The degradation of chlorophylls during heating cycles can be explained by the fact that these compounds are sensitive to higher temperatures as they are to light exposure [45,46]. Chlorophylls occur in cold-pressed plant oils; they are removed in the refining process.…”
Section: Conflicts Of Interestmentioning
confidence: 99%